Fine-Tuning ER Stress Signal Transducers to Treat Amyotrophic Lateral Sclerosis - Medinas, Danilo B.; González, Jose V.; Falcon, Paulina; Hetz, Claudio (Frontiers in Molecular Neuroscience, 2017)
Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease characterized by the progressive loss of motoneurons and paralysis. The mechanisms underlying neuronal degeneration in ALS are starting to be elucidated, highlighting disturbances in motoneuron proteostasis. Endoplasmic reticulum (ER) stress has emerged as an early pathogenic event underlying motoneuron vulnerability and denervation in ALS. Maintenance of ER proteostasis is controlled by a dynamic signaling network known as the unfolded protein response (UPR). Inositol-requiring enzyme 1 (IRE1) is an ER-located kinase and endoribonuclease that operates as a major ER stress transducer, mediating the establishment of adaptive and pro-apoptotic programs. Here we discuss current evidence supporting the role of ER stress in motoneuron demise in ALS and build the rational to target IRE1 to ameliorate neurodegeneration.